(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article examines the intricate relationship between access to justice and sustainable development, highlighting barriers to access to justice and the importance of alternative methods of conflict resolution. The study begins with an analysis of access to justice, identifying significant obstacles, particularly for vulnerable groups. It then explores how Sustainable Development Goal 16 (SDG 16), which aims to promote peace, justice, and strong institutions, is inherently linked to the principle of access to justice. The challenges faced in implementing each of the SDG 16 goals are highlighted. Furthermore, the article emphasizes the importance of access to justice as an essential facilitator for sustainable development, highlighting the promotion of sustainable practices as a key strategy to overcome existing barriers and foster a more equitable and inclusive world. This theoretical research will be conducted through the application of the inductive method, a descriptive approach, using bibliographic studies, electronic documents, journals, and other periodicals to bring forth respective reflections on the subject.